Synthesis of 4” manipulated Lewis X trisaccharide analogues - Moore, Christopher J.; Auzanneau, France-Isabelle (Beilstein Journal of Organic Chemistry, 2012)
Three analogues of the Lex trisaccharide antigen (β-D-Galp(1→4)[α-L-Fucp(1→3)]-D-GlcNAcp) in which the galactosyl residue is modified at O-4 as a methyloxy, deoxychloro or deoxyfluoro, were synthesized. We first report the preparation of the modified 4-OMe, 4-Cl and 4-F trichloroacetimidate galactosyl donors and then report their use in the glycosylation of an N-acetylglucosamine glycosyl acceptor. Thus, we observed that the reactivity of these donors towards the BF3·OEt2-promoted glycosylation at O-4 of the N-acetylglucosamine glycosyl acceptors followed the ranking 4-F > 4-OAc ≈ 4-OMe > 4-Cl. The resulting disaccharides were deprotected at O-3 of the glucosamine residue and fucosylated, giving access to the desired protected Lex analogues. One-step global deprotection (Na/NH3) of the protected 4”-methoxy analogue, and two-step deprotections (removal of a p-methoxybenzyl with DDQ, then Zemplén deacylation) of the 4”-deoxychloro and 4”-deoxyfluoro protected Lex analogues gave the desired compounds in good yields.
Keywords: chlorodeoxygalactose; fluorodeoxygalactose; Lewis X analogues; oligosaccharide synthesis